Coherent somatic mutation in autoimmune disease. - Kenneth Andrew Ross (Public Library of Science (PLoS), 2014)
Background Many aspects of autoimmune disease are not well understood, including the specificities of autoimmune targets, and patterns of co-morbidity and cross-heritability across diseases. Prior work has provided evidence that somatic mutation caused by gene conversion and deletion at segmentally duplicated loci is relevant to several diseases. Simple tandem repeat (STR) sequence is highly mutable, both somatically and in the germ-line, and somatic STR mutations are observed under inflammation. Results Protein-coding genes spanning STRs having markers of mutability, including germ-line variability, high total length, repeat count and/or repeat similarity, are evaluated in the context of autoimmunity. For the initiation of autoimmune disease, antigens whose autoantibodies are the first observed in a disease, termed primary autoantigens, are informative. Three primary autoantigens, thyroid peroxidase (TPO), phogrin (PTPRN2) and filaggrin (FLG), include STRs that are among the eleven longest STRs spanned by protein-coding genes. This association of primary autoantigens with long STR sequence is highly significant (p<3.0x10(-7)). Long STRs occur within twenty genes that are associated with sixteen common autoimmune diseases and atherosclerosis. The repeat within the TTC34 gene is an outlier in terms of length and a link with systemic lupus erythematosus is proposed. Conclusions The results support the hypothesis that many autoimmune diseases are triggered by immune responses to proteins whose DNA sequence mutates somatically in a coherent, consistent fashion. Other autoimmune diseases may be caused by coherent somatic mutations in immune cells. The coherent somatic mutation hypothesis has the potential to be a comprehensive explanation for the initiation of many autoimmune diseases.